Effect of phosphorus and gallium on oxidation resistance of Sn-0.7Cu brazing metal: First-principle calculation and experimental verification - Lingyue Wang; He Wei; Chen Liu; Shiyu Yang; Zulai Li; Min Zha (Journal of Materials Research and Technology)
In this paper, the mechanism of the effect of phosphorus and gallium on the oxidation resistance of Sn-0.7Cu brazing alloy was studied based on the calculation of first principles. The calculation shows that the control principle of the anti-oxidation of phosphorus and gallium is that a passivation film is formed on the surface of the substrate, which prevents the subsequent reaction of oxygen in the air with the substrate. Although phosphorus has been shown to be more electronegative, the antioxidant effect of gallium is stronger than that of phosphorus at medium and low oxygen concentrations, because gallium has a lower free energy and is more easily enriched near the passivation film from a kinetic point of view, and its ability to form an oxide layer is stronger than that of phosphorus. The enrichment of doping elements near the passivated film and the antioxidant effect were confirmed by experiments.